Validation of step time and asymmetry detection algorithm in high-intensity running with Movesense IMU - Martín Gómez, R.; Kamstra, H.; Allevard, E.; Pollet-Villard, L.; Cotter, J.; Lamb, P. (Journal of Biomechanics, 2025)
Movesense devices are open-source, low-cost, programmable with Bluetooth capability, offering applications from performance analysis to injury monitoring. Within a wider project aimed at developing comprehensive and freely-available assessment of human movement using wearable devices, this study aims to evaluate the validity and reliability of Movesense Inertial Measurement Units (IMUs) and novel algorithms for measuring step time and its right-left asymmetry during running. Data were collected using an app connected to the IMUs with custom firmware installed. The results were compared with those from a standard force plate system.